Variability of the active hydraulic downforce system related to cotton seed depth and emergence - Oliveira, L. [UNESP]; Ortiz, B.; Silva, R. [UNESP]; Pate, G.; Stafford, J. V. (Wageningen Acad Publ, 2021)
Hydraulic downforce system helps to maintain a target gauge wheel load on individual planter row units using fixed loads (manual mode) and automatically adjusting loads according to field variability (automatic mode). This work aimed to verify if the operational quality of cotton sowing changes when using the automatic or manual modes compared with no downforce, as well as to verify if the variability created by downforce levels can influence cotton seeding depth and emergence. For each operational mode, five load levels were tested and one control. More out-of-control observations were found while using lower loads and the greatest number was found while not using downforce. Planting process was more uniform when the automatic mode was used compared to manual mode and both exhibited better quality when compared to no downforce use. There was positive correlation between downforce level and seeding depth.
Keywords: downforce; statistical process control; cotton